Timeline of diagnosed pain causes in children with severe neurological impairment - Peri, Francesca; Magni, Elena; Pigani, Filippo; Romoli, Raffaella; Vetrella, Simona; De Zen, Lucia; Sagredini, Raffaella; Barbi, Egidio; Cozzi, Giorgio (Frontiers in Pediatrics, 2024)
Objective: Pain's causes in children with severe cognitive impairment may be challenging to diagnose. This study aimed to investigate if there is a relationship between pain causes and the age of children.We conducted a multicenter retrospective study in three Italian Pediatric Units. Eligible subjects were patients from 1 to 18 years with severe neurological impairment. We collected data regarding diagnoses, pain causes and medical or surgical procedures. The timing of pain episodes was categorized into age-related periods: infants and toddlers (0 -24 months), preschool children (3-5 years), schoolchildren (6-12 years), and adolescents (13-17 years).Results: Eighty children with severe neurological impairment were enrolled. The mean age was 11 years (±5.8). Gastroenterological pain was most common in the first years of life (p=0.004), while orthopaedic and tooth pain was the most typical in schoolchildren and adolescents (p=0.001 and p=0.02). Concerning surgical procedures, PEG placement and gastric fundoplication were significantly more common in the first 5 years of age (p=0.03), and heart surgery was typical of infants (p=0.04). Orthopaedic surgery was more commonly reported in older children and adolescents (p<0.001).Conclusions: Some causes of pain are more frequent in children with severe neurological impairment in defined age-related periods. Specific age-related pain frequencies may help physicians in the diagnostic approach.